SAT0314 IMPLEMENTATION OF AN ASSESSMENT CHECKLIST FOR PATIENTS WITH SPONDYLOARTHRITIS IN DAILY PRACTICE. (June 2019) - RAQUEL, ALMODOVAR; Joven-Ibáñez, Beatriz; Almaraz, Esther Rodríguez; Melchor, Sheila; Rabadan, Elena; Villaverde, Virginia; Navio, Mª Teresa; Cebrian, Laura; Lojo, Leticia; Prada-Ojeda, Alejandro; González, Laura; Martos, Álvaro García; et al.
Abstract : Background: Nowadays, despite international and national guidelines on the evaluation and management of spondyloarthritis (SpA), several studies have depicted a sub-optimal assessment of these diseases. Objectives: To analyze the feasibility and changes in the collection of clinical measures after the implementation in daily practice of a checklist designed for an optimal evaluation and monitoring of patients with SpA, including psoriatic arthritis (PsA). Methods: An observational prospective study was performed. The feasibility of the assessment checklist (paper/on-line format) for patients with SpA was tested (time to complete the checklist, simplicity, amenity clarity, usefulness). Through a medical files review, changes in the number of the checklist variables collected were analyzed previous to the implementation of the checklist and 6 months later. A descriptive and bivariate analysis was performed. Results: A total 6 hospitals and 11 rheumatologists participated. The median time to checklist completion was 15 (12-20) minutes, and the mean scores for the rest of variables of the feasibility test were in general positives, 6.9±1.1 (simplicity) and 6.9±0.8 (amenity), to 7.5±1.2 (clarity) and 7.5±1.4 (usefulness). A total of 83 and 68 medical files pre-implementation and post-implementation were reviewed respectively. Patient's features were similar. Mean age at diagnosis was 42.3±1.6 and 40.3±1.3 years respectively. In both study samples around a half of patients were men, and axial SpA and PsA were equally distributed as well (40.2% and 44.8% pre- and post-implementation (47.6% and 47.8%). We observed a significant increase in the collection of many of the checklist variables after the implementation. The record of BASDAI increased from 46.2% to 73.1% (p=0.001), physical activity from 48.2% to 88.2% (p<0.0001), physician global (VAS) from 28.0% to 73.5% (p<0.0001), patient global (VAS) from 48.8% to 85.3% (p<0.0001), morning stiffness from 62.8% to 84.8% (p=0.003), ASDAS (in axial SpA) from 12.2% to 32.8% (p=0.002), BASFI from 43.7% to 65.7% (p=0.008), or DAS28 (in PSA) from 24.7% to 46.3% (p=0.006). The record of extra-articular symptoms and signs and all of the comorbidities but for osteoporosis and peptic ulcer significantly improved too. The percentage of change ranged from 20% (extra-articular symptoms and signs or arterial hypertension) to 30% (diabetes mellitus, hyperlipidemia, gout/hyperuricemia and renal failure. Other checklist variables increased but not significantly. However, some of them like the HLA-B27 or work status were already recorded (before the implementation of the checklist) in the 82.3% and 95.2% of medical files respectively. Changes were observed irrespectively of SpA classification. Conclusion: The implementation of an assessment checklist in daily practice is feasible and improve the assessment of SpA patients. Acknowledgement: To María Jesús García de Yébenes for her methodological support. Disclosure of Interests: RAQUEL ALMODOVAR: None declared, Beatriz Joven-Ibáñez Speakers bureau: Celgene, Novartis, MSD, Pfizer, AbbVie, and Janssen, Esther Rodríguez Almaraz: None declared, Sheila Melchor: None declared, Elena Rabadan: None declared, Virginia Villaverde: None declared, Mª Teresa Navio: None declared, Laura Cebrian: None declared, Leticia Lojo: None declared, Alejandro Prada-Ojeda: None declared, Laura González: None declared, Álvaro García Martos: None declared, Victoria Navarro-Compán: None declared, Estíbaliz Loza Grant/research support from: Roche, MSD, Pfizer, Abbvie, BMS, UCB, Actelion, Celgene, Grunenthal and Sanofi, Pedro Zarco-Montejo: None declared